THE DEVELOPMENT HANDOUT Excoecaria agallocha (Buta Buta) IN MANGROVE AREA COASTAL OF SUNGAI RASAU AS ENHANCEMENT FOR BIODIVERSITY CONCEPT IN SENIOR HIGH SCHOOL - Madina Aulia; Bunda Halang; Hardiansyah Hardiansyah (Universitas Negeri Padang, 2021)
Teaching materials based on local potential are teaching materials that use the surrounding environment as a learning resource, one of which is a handout. Buta Buta plants are regional potentials that can be utilized by educators as material for enriching biodiversity that students learn in high school in the subject of Biology.The research and development aim to analyze the development of the Blinding Tree (Excoecaria Agallocha) handout in in the Sungai Rasau Mangrove Area as an EnrichmentMaterial for the Concept of Biodiversity in HighSchool. The development model uses Tessmer (1998) to the stage of self-evaluation and expert review. The research and development method used the development steps of the handout, the data analysis of the validity of the Blinding tree (Excoecaria agallocha) plant handout by using the validity score formula which includes 3 aspects of feasibility, namely aspects of content feasibility, presentation feasibility and language assessment. The results of the assessment of the validity of the handouts that were developed were stated to be very valid by obtaining an average score on the aspect of content feasibility, namely 87.5%, the average score in the aspect of feasibility of presentation was 93.33%, and the average score on the aspect of language assessment was 90.37% so that the handouts that have been developed can be used as material for enriching the concept of Biodiversity in High School.